2008
DOI: 10.1097/nmd.0b013e31815fa4c1
|View full text |Cite
|
Sign up to set email alerts
|

Core Schemas and Suicidality in a Chronically Traumatized Population

Abstract: The Young Schema Questionnaire (YSQ) has been demonstrated to tap into core beliefs, or maladaptive schemas, of clinical populations. This study used the YSQ to investigate maladaptive schemas of 137 chronically traumatized patients seeking outpatient psychiatric treatment and to assess whether specific schemas might be associated with suicide risk in this population. Participants completed a modified version of the YSQ-S (short form), post-traumatic diagnostic scale, dissociative experiences scale and self-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
52
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 22 publications
11
52
0
9
Order By: Relevance
“…Findings of researches confirm a relation between EMSs and depression disorder (Abela, Auerbach, Sarin, & Lakdawalla, 2009;Lumley & Harkness, 2007;Riso & Newman, 2003). Moreover, patients suffering from anxiety disorders obtained higher scores in a number of EMSs (Brewin, Andrews, & Valentine, 2000;Cockram, Drummond, & Lee, 2010;Delattre et al, 2004;Dutra, Callahan, Forman, Mendelsohn, & Herman, 2008;Hedley, Hoffart, & Sexton, 2001;Hinrichsen, Waller, & Emanuelli, 2004;Pinto-Gouveia et al, 2006). As mentioned above, findings show that EMSs varies in different disorders.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Findings of researches confirm a relation between EMSs and depression disorder (Abela, Auerbach, Sarin, & Lakdawalla, 2009;Lumley & Harkness, 2007;Riso & Newman, 2003). Moreover, patients suffering from anxiety disorders obtained higher scores in a number of EMSs (Brewin, Andrews, & Valentine, 2000;Cockram, Drummond, & Lee, 2010;Delattre et al, 2004;Dutra, Callahan, Forman, Mendelsohn, & Herman, 2008;Hedley, Hoffart, & Sexton, 2001;Hinrichsen, Waller, & Emanuelli, 2004;Pinto-Gouveia et al, 2006). As mentioned above, findings show that EMSs varies in different disorders.…”
supporting
confidence: 61%
“…However some researches can be mentioned in this filed such as Delattre et al (2004) about EMSs of anxiety disorders (Delattre et al, 2004); Hedley et al (2001) and Kwak & Lee (2015) about schemas of panic disorder (Hedley et al, 2001;Kwak & Lee, 2015); Hinrichsen (2004) (Hinrichsen et al, 2004) and Pinto Gouveya et al (2006) (Pinto-Gouveia et al, 2006) about EMSs of social anxiety disorder; Edworthy et al (2008) (Edworthy, Chasey, & Williams, 2008), Dutra et al (2008) (Dutra et al, 2008), and Cockram et al (2010) (Cockram et al, 2010) about EMSs of post-traumatic stress disorder; Atalay et al (2008) (Atalay, Atalay, Karahan, & Çaliskan, 2008), Noie et al (2009) (Noie, Farid, Fata, & Ashoori, 2010), Lochner et al (2005) (Lochner et al, 2005), Kim et al (2014) (Kim, Lee, & Lee, 2014) about EMSs of OCD disorder. Their most important limitations are as following: first, none of them is based on DSM-5 in which OCD is studied in a separate category from anxiety disorders; second, they do not compare OCD and anxiety disorders groups alongside a control group.…”
mentioning
confidence: 99%
“…The previous study had showed that EMSs were positively and significantly linked with suicide ideation (e.g. Dutra, Callahan, Forman, Mendelsohn, & Herman, 2008). This result confirmed the claim of Young, Klosko, and Weishaar (2003) that mentioned EMSs are self-destructive, affective and cognitive patterns and cause significant functional impairments during life.…”
Section: Discussionsupporting
confidence: 79%
“…Previous researches have shown that schemas of disconnection and rejection among other schemas have been more efficient in predicting suicide ideation (Dutra et al, 2008;Ahmadian Gorji et al, 2009), depression (Renner, Lobbestael, Peeters, Arntz, & Huibers, 2012) and neuroticism (Sava, 2009) that they are directly linked with suicide ideation. Thus, it can be concluded that the disconnection and rejection domain is a better predictor of suicide ideation than other domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation